A Study on Some Intuitionistic/Pythagorean Fuzzy Aggregation Operators - Garg, Diksha (My University, 2017)
In this thesis, need of intuitionistic/Pythagorean fuzzy aggregation operators is discussed. Furthermore, some existing properties of these aggregation operators as well as various extensions of these operators are studied.
Keywords: FUZZY SETS; AGGREGATION OPERATORS; INTUTIONISTIC OPERATORS; PYTHAGOREAN FUZZY OPERATORS; GEOMETRIC OPERATOR